Savanna burning, a controversial technique for rangeland management in the Niger flood plains of central Mali - Hiernaux, Pierre H.Y.; Diarra, L. (Australian Academy of Science, 1985)
Presents and discusses the results of a 3 year experiment carried - in the Niger flood plains of central Mali - to compare the effects of burning with cutting, grazing & complete exclosure. Makes suggestions for improved burning practices for range management.